The critical size of a defect in the glenoid causing anterior instability of the shoulder after a Bankart repair, under physiological joint loading. (January 2019) - Klemt, C.; Toderita, D.; Nolte, D.; Di Federico, E.; Reilly, P.; Bull, A. M. J.
Abstract : Aims: Patients with recurrent anterior dislocation of the shoulder commonly have an anterior osseous defect of the glenoid. Once the defect reaches a critical size, stability may be restored by bone grafting. The critical size of this defect under non-physiological loading conditions has previously been identified as 20% of the length of the glenoid. As the stability of the shoulder is load-dependent, with higher joint forces leading to a loss of stability, the aim of this study was to determine the critical size of an osseous defect that leads to further anterior instability of the shoulder under physiological loading despite a Bankart repair. Patients and Methods: Two finite element (FE) models were used to determine the risk of dislocation of the shoulder during 30 activities of daily living (ADLs) for the intact glenoid and after creating anterior osseous defects of increasing magnitudes. A Bankart repair was simulated for each size of defect, and the shoulder was tested under loading conditions that replicate in vivo forces during these ADLs. The critical size of a defect was defined as the smallest osseous defect that leads to dislocation. Results: The FE models showed a high risk of dislocation during ADLs after a Bankart repair for anterior defects corresponding to 16% of the length of the glenoid. Conclusion: This computational study suggests that bone grafting should be undertaken for an anterior osseous defect in the glenoid of more than 16% of its length rather than a solely soft-tissue procedure, in order to optimize stability by restoring the concavity of the glenoid.